Topology and Control Strategy of PV MVDC Grid-Connected Converter with LVRT Capability - Huan Wang; Yu Zhou; Xinke Huang; Yibo Wang; Honghua Xu (Applied Sciences, 2021)
This paper proposes an isolated buck-boost topology and control strategy for the photovoltaic (PV) medium-voltage DC (MVDC) converter with low-voltage ride through (LVRT) capability. The proposed isolated buck-boost topology operates on either boost or buck mode by only controlling the active semiconductors on the low-voltage side. Based on this topology, medium-voltage (MV) dc–dc module is able to be developed to reduce the number of modules and increase the power density in the converter, which corresponds to the first contribution. As another contribution, a LVRT method based on an LC filter for MVDC converter is proposed without additional circuit and a feedback capacitor current control method for the isolated buck-boost converter is proposed to solve the instability problem caused by the resonance spike of the LC filter. Five kV/50 kW SiC-based dc–dc modules and ±10 kV/200 kW PV MVDC converters were developed. Experiments of the converter for MVDC system in the normal and LVRT conditions are presented. The experimental results verify the effectiveness of the proposed topology and control strategy.